The perceptions of interns: exploring the organizational assimilation process of interns and the influence of organizational identity - Woo, Dajung (Kansas State University, 2012)
Internships provide students with valuable learning experiences in their chosen fields. Considering that one of the most important components of students’ learning experiences during an internship is learning how to socialize and assimilate into organizational settings, an internship stage model should be able to account for this particular process – organizational assimilation. This study contends that existing internship stage models overlap and can be enhanced by organizational assimilation theory (Jablin, 1987). Therefore, this qualitative study includes data from 13 semi-structured interviews with students who participated in formal internships in order to explore students’ assimilation experiences during the course of their internships. Additionally, how interns view the host organization’s identity and its impact on their assimilation experience was examined. Findings indicate that students are more adaptive to socialization than individualization in terms of their responsibilities and roles during organizational assimilation. Further, the concept of organizational identity was so complex and intricate that students could not grasp their host organizations’ identity during the course of their internships; instead, through their organizational assimilation experience, participants learned the culture of the organizations.
Keywords: Internship; Experiential education; Organizational assimilation; Organizational identity; Communication (0459)